Hallmarks of tax avoidance and tax evasion: a Malaysian perspective / Ahmad Syaiful Razli - Razli, Ahmad Syaiful (2015)
Tax is one important element in the Government of Malaysia's revenue. Each year, tax contributes to almost 80% of the Malaysian government's revenue. In order to have an efficient tax collection, the authorities need to ensure an acceptable level of tax compliance among the taxpayers. When discussing about tax compliance, noncompliance is an inevitable aspect. Compliance relates to the behavior of taxpayers, structure of the legal system that comprises of tax elements, the economic situation of the country and government policy on taxation. Taxpayers might put efforts to mitigate the risk or burden to pay taxes. Therefore, they might use legal and illegal ways to achieve their goal. Legal methods in reducing the amount of tax is called tax avoidance while tax evasion is illegal mean to avoid paying taxes.